Effects of pre- and post-natal lipid-based nutrient supplements on infant development in a randomized trial in Ghana. (August 2016) - Prado, Elizabeth L.; Adu-Afarwuah, Seth; Lartey, Anna; Ocansey, Maku; Ashorn, Per; Vosti, Steve A.; Dewey, Kathryn G.
Abstract: Background: Maternal and infant undernutrition is negatively associated with infant development. Aims: We tested the hypothesis that provision of small-quantity lipid-based nutrient supplements (SQ-LNS) to pregnant women and infants positively affects infant development. Study design: In a partially double-blind randomized controlled trial, we compared the following daily maternal supplements during pregnancy and until 6 months post-partum: iron/folic acid capsule (IFA), capsule containing 18 micronutrients (MMN), or 20 g SQ-LNS. Children in the SQ-LNS group also received SQ-LNS from age 6 to 18 months. The study is registered asNCT00970866 . Subjects: 1320 pregnant women in Ghana enrolled in the trial; 1173 of their children participated in developmental assessment. Outcome measures: We monitored the acquisition of 10 developmental milestones monthly by parental report, observed the attainment of 6 motor milestones at 6, 12, and 18 months, and conducted detailed assessment of motor, language, socio-emotional, and executive function at 18 months. Results: By researcher observation, a greater percentage of children in the SQ-LNS group (53%) was able to walk alone at 12 months than in the IFA group (43%; RR  = 1.23, 95% CI = 1.02–1.49; p  = 0.025). We found no significant differences between groups in milestone acquisition by parent report or in any scores at 18 months. The difference in mean z -scores between groups ranged from 0.03–0.13 for motor ( p  = 0.84), 0.01–0.08 for language ( p  = 0.46), 0.01–0.02 for socio-emotional ( p  = 0.75), and 0.00–0.02 for executive function ( p  = 0.95). Conclusion: While provision of maternal and child SQ-LNS in Ghana may affect walking at 12 months, it did not affect infant development at 18 months. Highlights: Few studies have examined the effects of combined pre- and post-natal nutritional supplementation on child development. A greater percentage of children who received SQ-LNS were able to walk at age 12 months, compared to a control group. At age 18 months, no differences were found between groups in motor, language, socio-emotional, or executive function scores.